2021
DOI: 10.21077/ijf.2021.68.3.108774-10
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-pathological changes in Indian catfish Clarias magur (Hamilton, 1822) upon experimental challenge with Aeromonas hydropila

Abstract: Motile Aeromonas septicaemia (MAS), caused by Aeromonas hydrophila, is one of the most significant problem among the bacterial diseases responsible for causing mortality in catfishes. The objective this study was to understand the modulation of innate immune parameters and histopathological alteration in Indian catfish Clarias magur (Hamilton, 1822), following intraperitoneal injection with A. hydrophila. At 3 to 8 h post-infection (hpi), respiratory burst activity, myeloperoxidase, protease, total anti-protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…EF‐1α was found to be the best candidate gene for analysis of Toll‐like receptor 3 and melanoma differentiation associated gene in CIK ( Ctenopharyngodon idella kidney) cell culture post Grass carp reovirus infection (Su et al, 2011). EF‐1α was used as RG for relative expression quantification of TLR2 and its downstream signalling molecule (Muduli, Paria, et al, 2021; Muduli, Rathore, et al, 2021). Paria et al (2016) also suggested EF‐1α and 18S to be the best RG in Asian seabass following V. alginolyticus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EF‐1α was found to be the best candidate gene for analysis of Toll‐like receptor 3 and melanoma differentiation associated gene in CIK ( Ctenopharyngodon idella kidney) cell culture post Grass carp reovirus infection (Su et al, 2011). EF‐1α was used as RG for relative expression quantification of TLR2 and its downstream signalling molecule (Muduli, Paria, et al, 2021; Muduli, Rathore, et al, 2021). Paria et al (2016) also suggested EF‐1α and 18S to be the best RG in Asian seabass following V. alginolyticus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Each sub‐group was maintained in three experimental tanks containing 10 fish each. Our previously isolated and characterized A. hydrophila strain 9C (Muduli et al, 2020, 2021b; Muduli, Rathore, et al, 2021) was used in this study. In A. hydrophila injected sub‐group, fish were injected with A. hydrophila at a concentration of 1 × 105 cfu/ fish in 100 µl PBS by intra‐peritoneal route.…”
Section: Methodsmentioning
confidence: 99%